2019
DOI: 10.1145/3359206
|View full text |Cite
|
Sign up to set email alerts
|

"Hello AI": Uncovering the Onboarding Needs of Medical Practitioners for Human-AI Collaborative Decision-Making

Abstract: Although rapid advances in machine learning have made it increasingly applicable to expert decision-making, the delivery of accurate algorithmic predictions alone is insufficient for effective human-AI collaboration. In this work, we investigate the key types of information medical experts desire when they are first introduced to a diagnostic AI assistant. In a qualitative lab study, we interviewed 21 pathologists before, during, and after being presented deep neural network (DNN) predictions for prostate canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
188
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 318 publications
(226 citation statements)
references
References 64 publications
5
188
2
Order By: Relevance
“…Research in HCI, and in particular Participatory Design (PD), has focused on shaping emergent technologies to support the practices and needs of those whose job it is to accomplish a given task or activity [13,14]. Recent studies in this area consider "acceptance" of algorithmic decision-support systems by practitioners [15]. Researchers looked at what information the practitioners desired when asked to make sense of an algorithmic diagnostic agent for decision-support in cancer diagnostics.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Research in HCI, and in particular Participatory Design (PD), has focused on shaping emergent technologies to support the practices and needs of those whose job it is to accomplish a given task or activity [13,14]. Recent studies in this area consider "acceptance" of algorithmic decision-support systems by practitioners [15]. Researchers looked at what information the practitioners desired when asked to make sense of an algorithmic diagnostic agent for decision-support in cancer diagnostics.…”
Section: Related Workmentioning
confidence: 99%
“…In the Cai et al [15] study, when asked about their desires the medical practitioners negotiated metrics of value and success for the diagnostic algorithmic agent. Some of these metrics would also apply to a human and follow the same logic as performance metrics.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of research addresses several critical design issues using, among others, more explainable AI frameworks [12], more precise data visualizations [13], and better presentation of information [27]. The second strand of research draws on the clinical appropriation of CDSTs to investigate the system as assistive and collaborative to the clinical routine [28]. Some early studies have explored HCI design strategies to fit intelligent systems into various clinical tasks.…”
Section: A Clinical Decision Support Systemsmentioning
confidence: 99%
“…Our results revealed that a chatbot with a passive type of interaction could be more efficient in assisting occupational health (OH) decision-making tasks. Some recent studies suggested that CDSTs should be designed to be unobtrusive [9], assistive [11], and collaborative [28]. Similarly, our CI mechanism with a passive assistant only provided on-demand feedback and lightweight information to assist with the consult without overburdening the concurrent tasks.…”
Section: A Fit Conversational Agents Into Oh Tasks As An Unobtrusivementioning
confidence: 99%